Comparison of the efficacy between olopatadine hydrochloride and desloratadine citrate disodium for chronic urticaria - WU Dandan; FU Xuhui; ZHAO Junlei; WANG Zhexin (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To compare the efficacy of olopatadine hydrochloride and desloratadine citrate disodium for the treatment of chronic urticaria. Methods A total of 184 patients with chronic urticaria were enrolled at the department of dermatology of Kaifeng People's Hospital from October 2020 to January 2024, and were randomly assigned into the study group (92 cases, olopatadine hydrochloride) and the controls (92 cases, desloratadine citrate disodium). Following one-month treatment, the clinical effective rate, symptom score, dermatology life quality index (DLQI) score and urticaria control test (UCT) score before and after the treatment, and adverse reactions were evaluated in both groups. Results After 1-month treatment, the total clinical effective rates were significantly higher in the study group than in the controls (95.65% vs. 86.96%, χ2=4.38, P=0.036). Moreover, the number and size of skin lesion, and itching severity were markedly lower in the study group (1.02±0.16 vs. 1.13±0.24 for lesion number; 0.88±0.18 vs. 0.96±0.13 for lesion size, and 0.88±0.21 vs. 0.97±0.25 for itching severity, P<0.01 for all). The DLQI score and UCT score also differed significantly between these two treatments (4.67±1.02 vs. 5.11±1.11 for DLQI and 12.01±1.89 vs. 10.98±2.41 for UCT, P<0.01 for both). The incidence rates of adverse reactions were similar between these two groups (4.35% vs. 5.43%). Conclusion Although both desloratadine citrate disodium and olopatadine hydrochloride are safe for chronic urticaria, olopatadine hydrochloride is more effective.